2010
DOI: 10.1590/s1516-31802010000500005
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of blood magnesium and phosphorus ion levels following thyroidectomy and correlation with total calcium values

Abstract: CONTEXT AND OBJECTIVE: Magnesium ion concentration is directly related and phosphorus ion concentration is inversely related to calcemia. The aim of this study was to evaluate the evolution of magnesium and phosphorus ion levels in patients undergoing thyroidectomy and correlate these with changes to calcium concentration. DESIGN AND SETTING:Prospective study at the Alpha Institute of Gastroenterology, Hospital das Clínicas, Universidade Federal de Minas Gerais. METHODS:The study included 333 patients, of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 7 publications
0
20
0
2
Order By: Relevance
“…In a previous paper, we reported hypomagnesemia (<0.7 mmol/L) to be a relatively common (12.9%) occurrence after thyroidectomy, and to be a strong predictor of post‐thyroidectomy hypocalcemia . Other authors have reported similar findings . In our previous paper, we examined the association between magnesium levels taken on the first postoperative day and incidence of biochemical and symptomatic hypocalcemia during the course of the 2‐night postoperative stay .…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…In a previous paper, we reported hypomagnesemia (<0.7 mmol/L) to be a relatively common (12.9%) occurrence after thyroidectomy, and to be a strong predictor of post‐thyroidectomy hypocalcemia . Other authors have reported similar findings . In our previous paper, we examined the association between magnesium levels taken on the first postoperative day and incidence of biochemical and symptomatic hypocalcemia during the course of the 2‐night postoperative stay .…”
Section: Introductionmentioning
confidence: 73%
“…Hypocalcemic patients also showed a significant drop in magnesium levels on POD2 from preoperative values; however, this drop was not significant among patients not developing hypocalcemia. In this study, there was no analysis performed for association between hypomagnesemia and hypocalcemia, or correlation between magnesium and calcium levels …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…PTH controls intestinal and renal absorption and excretion of phosphorus. PTH acts directly on proximal tubules of nephron and reduce phosphorus reabsorption and increasing phosphaturia (2,3). The drop in serum phosphorus in response to PTH stimulation is earlier than increase in calcium.…”
mentioning
confidence: 99%